2019
DOI: 10.3847/1538-4357/ab1eab
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Ratios in M10 Giants

Abstract: We measured carbon abundances and the 12 C/ 13 C ratio in 31 giant branch stars with previous CN and CH band measurements that span -2.33 < M V < 0.18 in the globular cluster M10 (NGC 6254). Abundances were determined by comparing CO features at ∼ 2.3 µm and specifically the 13 CO bandhead at 2.37 µm, to synthetic spectra generated with MOOG. The observed spectra were obtained with GNIRS on Gemini North with a resolution of R ≈ 3500. The carbon abundances derived from the IR spectra agree with previous [C/Fe] … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 91 publications
(142 reference statements)
3
8
0
Order By: Relevance
“…Note that the CN-w and the CN-s populations in our study correspond to the CN-Normal and the CN-Enhanced population byMaas et al (2019).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Note that the CN-w and the CN-s populations in our study correspond to the CN-Normal and the CN-Enhanced population byMaas et al (2019).…”
supporting
confidence: 51%
“…Recently, Maas et al (2019) reported carbon isotope ratios in giants stars in the globular cluster M10, finding that the decrement in the 12 C/ 13 C ratios both in the CN-w and the CN-s populations 3 in M10. They discuss further that to match their measurements of the surface carbon and carbon isotope ratios requires two different thermohaline mixing efficiencies.…”
Section: Synthetic Population Models and The Need For Extra Abundancementioning
confidence: 99%
“…The CNO surface abundances in evolved stars are modified by the nuclear burning together with internal mixing processes (Charbonnel 1994;Gratton et al 2000;Maas et al 2019). Therefore, dwarf stars are fundamentally indispensable to be observed in order to trace the CNO enrichment in the ISM.…”
mentioning
confidence: 99%
“…While La is marginally enhanced, Ce and Nd are found to be marginally under-abundant. (Spite et al 2006;Aoki et al 2007;Maas et al 2019). The dashed line at 12 C/ 13 C = 10 separates the groups "Mixed" and "Unmixed".…”
Section: Discussionmentioning
confidence: 99%